Clinical and Histopathological Prognostic Factors in Chondrosarcomas - Daugaard, Søren (Hindawi Publishing Corporation, 1997)
Purpose. In an attempt to identify clinical and histopathological factors of prognostic importance in chondrosarcomas, 115 cases of malignant and borderline chondromatous tumours were reviewed. Patients/methods. Histopathological features tested for prognostic information as well as reproducibility included cellularity, nuclear pleomorphism, multinucleated cells, mitotic activity and grade. Eleven patients had a biopsy only, and a short survival (median 2.0 years); these were excluded from further analysis. The remaining 104 patients who had received intended curative treatment had a median survival of 14.7 years. Results. In univariate analysis, tumour size, extra-compartmental growth, surgical margin and sex were significantly correlated to recurrence-free survival (RFS); sex was marginally significant while age, site and pathological parameters were not significant. Overall survival (OAS) was likewise found to be independent of pathological features as well as site, size and surgical margin; but age, sex and extra-compartmental growth were statistically significant. However, when the same parameters were entered into a stepwise Cox (multivariate) analysis, only surgical margin, cellularity and pleomorphism were significantly related to RFS; margin, grade, pleomorphism and age to OAS. Overall inter-observer agreement on grade was relatively low: 0.54, with a Kappa value of 0.32. It was not better for the other histological parameters, with the exception of the mitotic count. However, acceptable values were achieved when the material was divided into low-grade (grade I and below) vs high-grade (grade II and III) lesions: overall agreement 0.79, Kappa 0.56. Discussion. Although the grading of chondrosarcomas is in need of improvement, its replacement by semiquantitative evaluation of individual histopathological parameters as performed in this study offers no advantage. Among the clinical parameters, only the adequacy of the surgical treatment and the patient's age appear to be important.